Evaluation of Streptococcus pneumoniae as a cause of acute otitis media in Colombia: A prospective study - Wilfrido Coronell-Rodriguez; Rosanna Camerano; Juan Carlos Alvarado-Gonzalez; Alejandra Puerto; Josefina Zakzuk; Nelson R. Alvis-Zakzuk; Lina Moyano-Tamara; Sebastian Medina; Claudia Beltran; Maria Betancur; Monica Rojas; Luis Enrique Farias; et al. (PLoS ONE, 2025)
Objective Since the introduction of the pneumococcal conjugate vaccine PCV-10 in 2011 its impact on acute otitis media (AOM) in children under five years of age in Colombia was unknown. We aimed to describe the clinical and sociodemographic characteristics of a prospective cohort of patients between 3 and 59 months old attending a children’s hospital in Cartagena, Colombia. Methods A prospective cohort study was conducted over a 12-month period from August 5th, 2022 to August 5th, 2023. Diagnosis of AOM was confirmed by an otorhinolaryngologist. Middle ear fluid samples were obtained by swab or tympanocentesis, depending on the presence of spontaneous drainage. Samples with a positive culture for S. pneumoniae were sent to the Colombian National Health Institute for serotyping. We also estimated the prevalence of AOM caused by S. pneumoniae, the serotype distribution and antimicrobial resistance patterns. Results A total of 61 patients were enrolled, 58% were male, the median age was 12 months (IQR: 8–24). The most common isolated microorganisms were Pseudomonas aeruginosa (14.8%), methicillin-resistant Staphylococcus aureus (13.1%), and Streptococcus pneumoniae (9,8%). Six cases of S. pneumoniae were identified, median age was 26.5 months (IQR: 8–45), none had any comorbidities, and only one had a history of previous AOM episodes. Five of them were vaccinated. The serotype distribution was 19A (67%), 10F and 35A (17%) each. Within the antimicrobial resistance patterns, serotype 19A was multidrug resistant (resistance to: beta-lactams, macrolides, lincosamides and TMP/SMX). Conclusion S. pneumoniae continues to be a leading cause of AOM in our country. Serotype 19A accounts for 67% of these infections and exhibits a multidrug-resistant pattern similar to that observed in invasive pneumococcal disease. These findings are consistent with international data and provide a baseline for tracking future AOM trends related to S. pneumoniae after the introduction of the PCV-13 vaccine.